Beyond "Landscape" in REDD+: The Imperative for "Territory". (September 2016) - McCall, Michael K.
Highlights: Landscape is now the dominating boundary concept in REDD+ governance discourse. But landscape spatial units are not the management-administrative power space. "Territoriality" is required where forest lands are owned and managed by local people. "Landscape" does not address contestations around "whose territory?" A "landscape" lens disempowers local managers by framing forests as global good. Summary: This paper problematizes the use of the "landscape" concept as the perspective in forest governance and REDD+ discourse, especially as it affects ownership claims and management of forest space. This study advocates the contrasting concept of "territory" as essential to spatial justice in community-held forest lands and for effectivity in REDD+ projects. Whereas landscape in REDD+ discourse is a basic unit of resolution for biophysical, especially conservationist, analysis; territory refers to spatial units embedded in tenurial entitlements, and thus in governance and the execution of management. The study critically considers case studies and conceptual approaches in REDD+ and Climate Smart Landscapes projects and their commitment to landscape, or territory, as the spatial governance unit. The review highlights some promising partial steps toward "territorialization" as a good practice, but finds that most do not follow up the implications for governance. The paper asserts that "landscape" as an analytical understanding of forest peoples' space contains serious defects—it does not set up the essential architecture and mechanisms for social owning and holistic management of designated (forest) space as territory, it does not address the contestations around "whose territory?", and a "landscape" discourse can obfuscate the actual practice of REDD+ programs. "Territorialization" would involve situating legitimate land users' rights at the core of REDD+ spatial planning and implementation. "Forest landscapes as territories" would legitimize the entitlements of forest peoples to govern their own lands, with the responsibilities and rewards of their experience of effective management. The community and its social territorial space would become the definitive spatial unit for operationalizing REDD+, rather than the ecological unit or watershed, by prioritizing upwardly institutionalized territory over bio-physical spatializations of landscape. A territorial perspective should shift some power away from global and national policy-setters to local actors (not only registered landowners), as central in REDD+ governance.